Akbar : The Architect of the Mughul Empire - Qureshi, Ishtiaq Husain (Karachi, Pakistan Ma'Aref (Limited), 1987)
"This book portrays the complex character of a man who achieved a great deal within his life time. Yet he also laid the foundations of the decay of his great empire. His success gave peace and prosperity to the major part of the subcontinent; his failure to see events in their correct perspective laid the foundation of the enslavement not only of the Muslims of the subcontinent but the entire Muslim world."Keywords: MUGHAL EMPIRE AKBAR
Include Index
Keywords: Mogul Empire -- History -- Mogul Empire -- Kings and Rulers -- Biography -- Kings and Rulers